The Influence of Live Streaming and Content Marketing on Purchase Decision Through Brand Trust among TikTok Shop Users in Jakarta - Indah Syafitri; Dita Puruwita; Kusworo Kusworo (The Future of Education Journal, 2026)
The growth of TikTok Shop as a social commerce platform that integrates entertainment and shopping activities has significantly increased user interest. However, the growth in users has not been fully aligned with transaction levels, indicating the need to examine factors influencing consumer purchase decision. This study aims to analyze the effect of live streaming and content marketing on purchase decision with brand trust as a mediating variable among TikTok Shop users in Jakarta. This study employed a quantitative approach using purposive sampling involving 170 respondents aged 18-24 years who had made purchases through TikTok Shop. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 through outer model, inner model, and hypothesis testing. The results show that live streaming, content marketing, and brand trust have a positive and significant effect on purchase decision. Furthermore, brand trust significantly mediates the effects of live streaming and content marketing on purchase decision. Among the studied variables, live streaming has the most dominant influence in enhancing brand trust, which subsequently encourages consumer purchase decision. These findings indicate that interactive live streaming strategies supported by credible and engaging content marketing can strengthen brand trust and increase purchase decision on TikTok Shop.